Re-constructing the man of steel : Superman 1938-1941, Jewish American history, and the invention of the Jewish-comics connection /: Superman 1938-1941, Jewish American history, and the invention of the Jewish-comics connection. ([2016]) - Lund, Martin, 1984-
No abstract available